Znanost ni nepristranska – nemški nacionalizem na Inštitutu za geografijo Univerze v Gradcu s poudarkom na protislovenstvu - Čede, Peter; Fleck, Dieter (Slavia Centralis, 2025)
Science is not Unbiased – German Nationalism and Anti-Slovenian Attitudes in the Institute of Geography at the University of Graz. Čede and Fleck’s article translated from German (Čede, Fleck 2021) is a study on German nationalism at the Institute of Geography of the University of Graz. It focuses on anti-Slovenian topics, discussing Graz geographers who spoke about Slovenes or Slovenia under the influence of German nationalist mentality. The studied texts show that the authors were closely acquainted with German nationalist literature. Also the political and socio-cultural mentality that guided the authors’ research is now quite in the open. The study is based on hermeneutic textual interpretation.